Стійкість граничних циклів - Татаренко, Віталій Віталійович; Tatarenko, Vitalii (Харків : Харківський національний університет імені В.Н. Каразіна, 2024)
У кваліфікаційній роботі досліджуються на стійкість граничні цикли на площині, з’ясовується зв’язок орбітальної стійкості циклу зі стійкістю за Ляпуновим. Наведені приклади граничних циклів та дослідження на їх стійкість. Докладно розглянуто нелінійний осцилятор та дослідження умов, за якими він має стійкий граничний цикл. Крім того, розглянуто брюселятор - важливу математичну модель хімічної кінетики і теж наведені умови існування стійкого граничного циклу.

In the qualification work, stability of limit cycles on a plane is examined, and a connection between the orbital stability of the cycle and the Lyapunov stability is studied. We give examples of limit cycles and investigate their stability. The nonlinear oscillator and the investigation of conditions under which there is a stable limit cycle are thoroughly examined. In addition, the brusselator, which is an important mathematical model of chemical kinetics, is considered and conditions for existence of a stable limit cycle are also given.
Stability of limit cycles
Keywords: MATHEMATICS::Applied mathematics; система диференціальних рівнянь; граничний цикл; стійкість; system of differential equations; limit cycle; stability